The Relationship between Teacher-Student Interaction and Students’ Motivation in Junior High School EFL Classrooms - Songidah Songidah; Feisal Aziez; Rimajon Sotlikova (Universitas Pendidikan Ganesha, 2025)
This study examined the relationship between teacher–student interaction and students’ motivation in Junior High School English as a Foreign Language (EFL) classrooms. Motivation plays a vital role in the language learning process, influencing students’ engagement, persistence, and overall academic performance. Teacher–student interaction, which includes emotional support, classroom organization, and instructional support, has been identified as a significant factor in shaping students’ learning experiences. This research employed a quantitative correlational design, collecting data from 150 students and five teachers across four junior high schools in Ciamis, West Java. The instruments used were adapted from Pianta’s Classroom Assessment Scoring System (CLASS) and Gardner’s Attitude/Motivation Test Battery (AMTB), measuring various dimensions of teacher–student interaction and both integrative and instrumental types of student motivation. Data analysis was conducted using Pearson’s product-moment correlation, which revealed a positive and moderate correlation (r = 0.576) with a significance level of p < 0.05. The findings demonstrate that supportive and structured teacher–student interactions significantly enhance students’ motivation in EFL contexts. The study emphasizes the need for educators to foster emotionally supportive, well-organized, and cognitively stimulating classroom environments to promote student engagement and success. This research contributes to the existing literature by highlighting the importance of interaction quality in motivating students and suggests implications for teacher training and classroom management strategies in EFL settings.